Minat Baca Masyarakat saat Pandemi Covid-19 di Taman Baca Masyarakat MIZAN - Achmad, Ilmar Andi; Asmas, Muhammad Athar (Journal of Nonformal Education and Community Empowerment, 2021)
This research is a quantitative descriptive, where the problem in this writing is How is the Use of the Mizan Community Reading Park as a source of learning in increasing thecommunity's interest in reading in the Mannuruki urban village of Makassar ?. Thepurpose of writing is to describe the use of community reading parks as a source oflearning in increasing public interest in reading. The approach used in this paper isquantitative with quantitative descriptive research type, the population in this study is allvisitors to the Mizan community reading park as many as 480 people, the sample istaken ten percent of the existing population of 48 people, data collection techniques usingquestionnaire and technique techniques documentation, and data managementtechniques using descriptive this shows that many people who use the Mizan CommunityReading Park in the midst of a global pandemic that hit Indonesia.